Targeted Therapy in Oropharyngeal Squamous Cell Carcinoma: The Implications of HPV for Therapy - Hay, Ashley (Rare Cancers Ther, 2015)
Oropharyngeal cancers caused by human papillomaviruses (HPV) have a different epidemiology, prognosis, genetic mutational landscape, response to treatment, and outcome when compared to HPV-negative cancers. In this review, a summary of our current understanding of HPV in head and neck cancer and the important advances that have shown HPV to be an etiological agent are discussed. HPV-positive and HPV-negative tumors are compared discussing clinicopathological factors, prognosis, outcome following treatment, and the molecular and genetic differences. Currently, the standard of care for oropharyngeal cancer is both surgery and post-operative radiotherapy with or without cisplatin or concurrent chemo-radiotherapy. The latter is used more often, especially in cancers of tonsil and base of tongue. However, there is increased interest in trying to de-intensify treatment and in the development of new treatments to target the underlying different molecular pathways of HPV-positive cancers. The current clinical trials involving surgery, chemotherapy, and radiation therapy are discussed. The new targeted treatments are also summarized. Although there is currently is no evidence from prospective studies to support a change in the treatment algorithm, the treatment options for patients with HPV-positive disease are likely to change in the future.